Active suspension control algorithms for a four–wheel vehicle model. (4th August 2014) - Hady, M.B.A. Abdel; Crolla, D.A.
This paper gives a review of the application of linear optimal control theory to the design of control laws for an actively suspended vehicle. Both common descriptions of the road surface input, which assume that it can be modelled either as integrated while noise or altered white noise, are considered. Particular attention is paid to the problem of accounting in the control law for (a) the cross–correlation between left and right tracks and (b) correlation arising from the fact that the rear wheel is a delayed version of the front. Both the cases of full and limited state feedback are considered. It is shown that a control law with practical potential can be derived which uses limited slate feedback hereby avoiding the need to measure the ground input states and which accounts for cross–correlation and time delay features mentioned above.